Oxidized Dopamine Acrylamide Primer to Achieve Durable Resin–Dentin Bonding - Leping Wu; Hui Shao; Yang Tao; Jingya Wu; Xinhui Wang; Qiufeng Nian; Shunli Zheng; Chris Ying Cao; Yuancong Zhao; Zheng Zhou; Hai Ming Wong; Quan-Li Li (Research, 2023)
The durability of the resin–dentin bonding interface is a key issue in clinical esthetic dentistry. Inspired by the extraordinary bioadhesive properties of marine mussels in a wet environment, we designed and synthetized N-2-(3,4-dihydroxylphenyl) acrylamide (DAA) according to the functional domain of mussel adhesive proteins. DAA’s properties of collagen cross-linking, collagenase inhibition, inducing collagen mineralization in vitro, and as a novel prime monomer for clinical dentin adhesion use, its optimal parameters, and effect on the adhesive longevity and the bonding interface’s integrity and mineralization, were evaluated in vitro and in vivo. The results showed that oxide DAA can inhibit the activity of collagenase and cross collagen fibers to improve the anti-enzymatic hydrolysis of collagen fibers and induce intrafibrillar and interfibrillar collagen mineralization. As a primer used in the etch-rinse tooth adhesive system, oxide DAA can improve the durability and integrity of the bonding interface by anti-degradation and mineralization of the exposed collagen matrix. Oxidized DAA (OX-DAA) is a promising primer for improving dentin durability; using 5% OX-DAA ethanol solution and treating the etched dentin surface for 30 s is the optimal choice when used as a primer in the etch-rinse tooth adhesive system.